ҚАЗАҚ ҲӘМ ӨЗБЕК ӘДЕБИЯТТАНЫЎЫНДА СТИЛЬ МӘСЕЛЕСИНИҢ ИЗЕРТЛЕНИЎИ - Баўетдинов, М.К. (FAN va JAMIYAT, 2023)
The article examines the level of study of the problem of style in Kazakh and Uzbek literary studies. Mainly, the opinions of scholars were studied and analyzed such as Q.Jumaliev, Z.Qabdolov, Q.Mashhur-Jusipov in Kazakh literary studies, T.Boboev, H.Boltaboev, M.Davronova, D.Kuronov, U.Jo’rakulov in Uzbek literary studies.